Cloning and functional characterization of a fructan 1-exohydrolase (1-FEH) in edible burdock (Arctium lappa L.) - Onodera Shuichi; Yoshida Midori; Ishiguro Yojiro; Ueno Keiji; Shiomi Norio (Chemistry Central Journal, 2011)
Abstract Background We have previously reported on the variation of total fructooligosaccharides (FOS), total inulooligosaccharides (IOS) and inulin in the roots of burdock stored at different temperatures. During storage at 0°C, an increase of FOS as a result of the hydrolysis of inulin was observed. Moreover, we suggested that an increase of IOS would likely be due to the synthesis of the IOS by fructosyltransfer from 1-kestose to accumulated fructose and elongated fructose oligomers which can act as acceptors for fructan:fructan 1-fructosyltransferase (1-FFT). However, enzymes such as inulinase or fructan 1-exohydorolase (1-FEH) involved in inulin degradation in burdock roots are still not known. Here, we report the isolation and functional analysis of a gene encoding burdock 1-FEH. Results A cDNA, named aleh1, was obtained by the RACE method following PCR with degenerate primers designed based on amino-acid sequences of FEHs from other plants. The aleh1 encoded a polypeptide of 581 amino acids. The relative molecular mass and isoelectric point (pI) of the deduced polypeptide were calculated to be 65,666 and 4.86. A recombinant protein of aleh1 was produced in Pichia pastoris, and was purified by ion exchange chromatography with DEAE-Sepharose CL-6B, hydrophobic chromatography with Toyopearl HW55S and gel filtration chromatography with Toyopearl HW55S. Purified recombinant protein showed hydrolyzing activity against β-2, 1 type fructans such as 1-kestose, nystose, fructosylnystose and inulin. On the other hand, sucrose, neokestose, 6-kestose and high DP levan were poor substrates. The purified recombinant protein released fructose from sugars extracted from burdock roots. These results indicated that aleh1 encoded 1-FEH.